DIGITAL TRANSFORMATION POLICIES TO DEVELOP AN EFFECTIVE ECOSYSTEM: THE CASE OF UKRAIN - Alisa S. Mahdich; Oleksandr A. Zadoia (Êvropejsʹkij Vektor Ekonomìčnogo Rozvitku)
The article analyzes the evolutionary development and implementation of the digital transformation policy on the way to building the digital economy of Ukraine. The need to carry out reforms, improve the investment climate, and economic recovery prompted the state to develop a legal basis for future digital transformations in the development of the national ecosystem. Along with this, the above-mentioned steps contribute to the further integration of Ukraine into the EU. Using advanced technologies, such as artificial intelligence, blockchain, analysis of large data sets, and others, digitalization becomes a key driver in the creation of innovative products and services, which in turn increases the competitiveness and efficiency of the socio-economic model of the state as a whole. But with the beginning of a full-scale military invasion of the russian federation into Ukraine, the state is forced to look for non-standard solutions for the continuation of the digital transformation policy. Currently, the question arises of the need to conduct an in-depth analysis of the key elements of the ecosystem of IT startups and determine the role of the state in the use of relevant tools and reforms on the path of further effective digital transformation in all sectors of the economic complex. In the course of the research, it has been found that the scientific and technological potential in Ukraine continues to decline in the period after the signing of the Ukraine-EU Association Agreement. At the same time, the issue of innovative development of Ukraine has been in the center of attention of the government, a number of donor structures, and the expertscientific environment of Ukraine for the past several years. The Government of Ukraine has launched a number of initiatives aimed at creating opportunities for the development of the domestic ecosystem of innovations, information and communication technologies (ICT) and startups, among which such promising and ambitious projects as: “E-residency” (creating conditions for non-residents to conduct business in Ukraine without a physical presence on its territory), “Diia.City” (a unique legal and tax space for IT business in Ukraine, which aims to give companies and startups effective tools for intensive development, scaling and capitalization), an online platform of the current status of the Ukrainian IT ecosystem (will provide an opportunity to search for business information about IT companies, professionals, investors and, in general, the entire technological ecosystem of Ukraine), development of the Concept of the Development of Artificial Intelligence in Ukraine (covers 9 fields: education and science, economy, cyber security, information security, defense, public administration, legal regulation, justice) and others. According to the results of the study, it becomes clear that in the era of rapid technological progress, the development of digital technologies has transformed the way of doing business, making it more dynamic and global. Management of digital ecosystems requires the state to develop adequate legal and regulatory frameworks. Intensive cooperation and financial support, even under martial law, will allow Ukraine to actively develop infrastructure, promote digital transformation, strengthen technological potential, sustainable economic recovery and deepen integration into the European digital market. Currently, there is no doubt about the need to strengthen efforts to implement current and prospective programs of digital reform of the ecosystem of Ukraine.